Rituals and Ceremonies of Quality of Higher Education. New Academic Tribes and Challenges in Social Recognition - Arias, César Correa (Richtmann Publishing, 2012)
Quality has been the most relevance public policy on higher education worldwide in about three decades. Quality is, primarily,a product of a linear equation of an overall expansion and massification of higher education since the 1970s, and the lack of resources toensure a long-term educational support. Therefore, it is evident the design and implementation of a public policy without a critical debateabout the implications for the entire educational systems. Secondly, it implies a qualitative change in the process of evaluation from apedagogical process based on significant curricular experiences, to the construction of a positivist system of evidence for each potentialor de facto act of learning, producing an institutional evaluation based on productivity, competitiveness, achievement and treasure ofeconomical, social and cultural capitals. It is about a substantial change in the concepts and practices of educational administration froman academic/knowledge regime to academic/knowledge capitalism regime, corporatizing educational institutions and promoting socialfragmentation. Testimonies from scholars in facing this academic regime show a relevant erosion of the academic work and an epistemicreduction of educational disciplines, making the policy of quality of education, more than a well-intentioned educational improvement, asource of deinstitutionalization, discrimination and practices of social control and lack of social recognition.This work analyzes socialconfigurations from scholars’ experiences in Higher Education in Mexico facing the rhetoric and procedures of quality of education.Through ethnography and phenomenological hermeneutics analysis this research shows imaginaries that deform scholars’ educationalpractices and a consequent ideological social recognition.